Metal Immiscibility Route to Synthesis of Ultrathin Carbides, Borides, and Nitrides. Issue 29 (8th June 2017) - Wang, Zixing; Kochat, Vidya; Pandey, Prafull; Kashyap, Sanjay; Chattopadhyay, Soham; Samanta, Atanu; Sarkar, Suman; Manimunda, Praveena; Zhang, Xiang; Asif, Syed; Singh, Abhisek K.; Chattopadhyay, Kamanio; et al.
Abstract : Ultrathin ceramic coatings are of high interest as protective coatings from aviation to biomedical applications. Here, a generic approach of making scalable ultrathin transition metal‐carbide/boride/nitride using immiscibility of two metals is demonstrated. Ultrathin tantalum carbide, nitride, and boride are grown using chemical vapor deposition by heating a tantalum‐copper bilayer with corresponding precursor (C2 H2, B powder, and NH3 ). The ultrathin crystals are found on the copper surface (opposite of the metal–metal junction). A detailed microscopy analysis followed by density functional theory based calculation demonstrates the migration mechanism, where Ta atoms prefer to stay in clusters in the Cu matrix. These ultrathin materials have good interface attachment with Cu, improving the scratch resistance and oxidation resistance of Cu. This metal–metal immiscibility system can be extended to other metals to synthesize metal carbide, boride, and nitride coatings. Abstract : Ultrathin tantalum carbide, nitride, and borides are synthesized on the surface of copper by heating a copper‐tantalum immiscible couple in a precursor gas (C2 H2, NH3, or B). This growth is caused by the immiscibility of the metals, which only allows clusters of Ta to migrate through the Cu matrix. These ultrathin crystals can increase the oxidation and wear resistance of copper.